2023
DOI: 10.35848/1347-4065/acb953
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective isotropic gas-phase etching of SiO2 using HF and methanol at temperatures –30 °C and lower

Abstract: The gas-phase etching of SiO2 was examined using HF and methanol vapor at low temperature below 0 °C and at low pressure. The etching rate of SiO2 increased with decreasing temperature and showed a maximum around –30 °C. The obtained etching rate was maximum 40 nm/min at plasma-enhansed CVD SiO2. The etching rate of SiN examined for comparison was less than 10 times smaller than that of SiO2 in this condition. As a result, the etching selectivity of SiO2 to SiN was found to be over 20 at –40 °C. Utilizing low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…2.1. System set-up and process flow of gas-phase etching Gas-phase etching was carried out using the dry chemical removal (DCR) system described in our previous paper 46) The system has infrared (IR) lamps and an electric static chuck (ESC) stage to enable the provision of rapid heating and cooling. Since a low-temperature chiller was also installed to cool the ESC stage, the wafers can be cooled down to -50 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1. System set-up and process flow of gas-phase etching Gas-phase etching was carried out using the dry chemical removal (DCR) system described in our previous paper 46) The system has infrared (IR) lamps and an electric static chuck (ESC) stage to enable the provision of rapid heating and cooling. Since a low-temperature chiller was also installed to cool the ESC stage, the wafers can be cooled down to -50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper 46) we investigated isotropic gas-phase etching for SiO 2 by HF and methanol at low temperatures below 0 °C and at a low pressure of 300 Pa to achieve rapid and highly selective isotropic etching for SiO 2 . We found that the etching rate for SiO 2 was enhanced with decreasing temperature and showed a maximum value at around -30 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attempts have been made to study low-temperature etching. Recent studies focusing on etching thin films of SiO 2 and SiN at low temperatures have shown intriguing results via different etching mechanisms compared to those at room temperature [ 7 , 8 , 9 ]. However, examples of related research on the aspect ratio etching of SiO 2 are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas 19,20 On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. 21,22 In the present work, CF 4 and HF plasma discharges diluted with H 2 were utilized to etch the SiN films prepared by plasmaenhanced chemical vapor deposition (PECVD). To elucidate the role of hydrogen, the chemical properties of the CF 4 /H 2 and HF/H 2 plasmas were investigated by means of optical emission spectroscopy and optical actinometry techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has also been reported that high SiN/SiO 2 selectivity can be achieved using gas mixtures such as NF 3 /O 2 or CF 4 /N 2 /O 2 plasmas, which is attributed to the influence of NO radicals. , The addition of hydrogen to fluorocarbon gas, leading to the generation of CH x F y ions, can be used to enhance the etch rate (ER) and/or selectivity of SiN/SiO 2 or SiN/Si. Special hydrofluorocarbon gases have been used to achieve high etch selectivity for SiN over SiO 2 and Si. Additionally, the dependence of selectivities between Si-based materials on substrate temperature has recently been investigated by various research groups. , In hydrogen-contained fluorocarbon plasmas, the formation of hydrogen fluoride (HF) is anticipated to have a detrimental effect on etching for Si-based materials, as it tends to scavenge F radicals . In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. , Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas , On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. , …”
Section: Introductionmentioning
confidence: 99%